Frutose-1,6-bisfosfato e N-acetilcisteína atenuam a formação de produtos proteicos de oxidação avançada, uma nova classe de mediadores inflamatórios, in vitro - Bochi, Guilherme Vargas (2012)
The assessment of biomarkers of reactions involving reactive oxygen species have the potential not only to determine the extent of oxidative damage, but also to predict the effectiveness of therapeutic strategies aimed at reducing or preventing the damage promoted by oxidative stress. Recently, it has been described and characterized a new class of compounds formed in consequence of oxidative stress, designated as advanced oxidation protein products (AOPP). The accumulation of AOPP was first described in patients with chronic renal failure undergoing hemodialysis and was subsequently found in diabetes, atherosclerosis, obesity and acute renal failure. Previous studies have identified AOPP as a new marker of oxidative damage to proteins and a new class of inflammatory mediators, providing arange of effects at both the cellular and systemic levels. Although the mechanism of action by which AOPP act is not fully understood, it is known that these products activate respiratory burst in phagocytes, including neutrophils and monocytes, through the activation of enzymes present in these cells. Furthermore, it has been demonstrated that AOPP may promot these effects (pro-oxidants and pro-inflammatory) at several cell types such as endothelial and kidney cells via activation of a signaling cascade, and in some aspects of this cascade AOPP effects is very similar to effects caused by advanced glycation end products (AGEs). In this context, the evaluation of the antioxidant activity of compounds in vitro models involving the formation of AOPP may present special interest. Among these compounds, N-acetylcysteine (NAC) and Fructose-1 ,6-bisphosphate (FBP) may be promising substances for this purpose. The NAC is a sulfhydryl donor group very similar to the amino acid cysteine and FBP is a highly energetic intermediate metabolite of glycolysis. Thus, the aim of this study was to determine the effects of FBP and NAC, as well as the synergistic effect of both treatments on the formation of AOPP in vitro. For this purpose, purified human albumin was incubated with various concentrations of hypochlorous acid (HOCl) (1, 2 and 4 mM) to produce AOPP in vitro, which was named albumin-advanced oxidation protein products (albumin-AOPP). In this context, both FBP as NAC were able to inhibit the formation of AOPP concentration-dependent manner, with FBP 20mg/mL and NAC 1mg/mL were responsible for the inhibition of 64% and 85% respectively. Furthermore, the synergistic effect promoted by the association of both compounds was more effective ininhibiting the formation of AOPP. Therefore, FBP and NAC may be promising candidates to mitigate or neutralize the pro-inflammatory and pro-oxidant triggered by AOPP.